Decellularized natural 3D cellulose scaffold derived from Borassus flabellifer (Linn.) as extracellular matrix for tissue engineering applications. (15th November 2021) - Mahendiran, Balaji; Muthusamy, Shalini; Selvakumar, R.; Rajeswaran, Narmadha; Sampath, Sowndarya; Jaisankar, S.N.; Krishnakumar, Gopal Shankar
Abstract: In this study, Borassus flabellifer (Linn.) (BF) immature endosperm was decellularized to produce three dimensional (3D) cellulose scaffolds that can support mammalian 3D cell culture. To this regard, we first evaluated the chemical composition, nutritive profile and pharmacological activities of BF endosperm. The results demonstrated that the BF tissue represented a complex concoction of polysaccharides with intrinsic phyto-ingredients which provide excellent pharmacological properties. Furthermore cellulosic scaffolds (CS) obtained from BF was treated with chitosan to produce cellulose-chitosan (CS/CHI) hybrid scaffolds. The comparative investigation on both scaffolds exhibited adequate swelling with controlled porosity and pore-size distribution. The physiochemical characterization showed reduced biodegradation, improved thermal stability and enhanced compressive strength in CS/CHI group. Biological studies reported favorable adhesion and proliferation of fibroblasts with evident cellular penetration and colonization on the both scaffolds. Taken together, plant derived cellulosic scaffolds could be used as an alternative scaffolding material in regenerative medicine. Graphical abstract: Unlabelled Image Highlights: Development of cellulosic scaffolds from plant native structure for tissue repair Improving the bio functionality of cellulosic scaffolds with chitosan treatment Scaffolds exhibited suitable physiochemical and morphological features Chitosan incorporation improved the mechanical and biodegradation properties Scaffolds supported fibroblast adhesion, migration and proliferation